Cadmium Exposure Induces Inflammation Through Oxidative Stress-Mediated Activation of the NF-κB Signaling Pathway and Causes Heat Shock Response in a Piglet Testis - Li, Yulong; Wang, Hongbao; Wang, Yanfei (Biological trace element research, 2025)
Cadmium (Cd), recognized as an environmental toxin, can cause injury to the testis in humans and animals. Oxidative stress (OS) can trigger an inflammatory response by promoting the activation of nuclear factor kappa beta (NF-κB) signaling pathway. Meanwhile, inflammation can lead to the occurrence of heat shock reaction. Yet, the specific mechanism by which Cd causes testicular injury in piglets, as well as the roles of oxidative stress, NF-κB signaling pathway, and heat shock response, still remained unclear. In this study, 6-week-old male piglets were selected as the experimental subjects, and the testicular injury model was developed by adding CdCl 2 (20 mg/kg) to the feed. After 40 days, piglets were euthanized, and testis tissues were collected for the following experimental analysis (the ultrastructural characteristics, antioxidant levels, trace element concentrations, and molecular-level changes). The findings displayed that Cd exposure caused the widening of the perinuclear space and the fragmentation of the nuclear membrane in testis. In addition, Cd exposure increased the contents of Cd, iron (Fe), and manganese (Mn), while the contents of selenium (Se), calcium (Ca), zinc (Zn), and copper (Cu) were reduced in testis. The activities of oxidative enzymes inducible nitric oxide synthase (iNOS), hydrogen peroxide (H 2 O 2 ), malondialdehyde (MDA), and nitric oxide (NO) were enhanced in testis after Cd exposure; meanwhile, the activities of antioxidant enzymes catalase (CAT), glutathione (GSH), glutathione peroxidase (GSH-PX), superoxide dismutase (SOD), and total antioxidant capacity (T-AOC) were reduced. And Cd exposure led to an upregulation of NF-κB, iNOS, interleukin 6 (IL-6), and cyclooxygenase-2 (COX-2) at both the mRNA and protein levels and increased the fluorescence intensity of the heat shock proteins (HSPs) HSP60, HSP70, and HSP90 in the testis. Altogether, Cd exposure induced toxic damage to piglet testis and potentially triggered inflammation through the oxidative stress/NF-κB signaling pathway and then resulted in heat shock response.